Gastrointestinal Parasites of Cattle in Central Java - Hamid, Penny Humaidah; Kristianingrum, Yuli Purwandari; Prastowo, Joko; Ribeiro da Silva, Liliana Machado (Science Publication, 2016)
Gastrointestinal parasites are the main cause of losses of cattle farms including feed conversion-failure and even death of heavily infected animals. We have conducted a random examination of 455 cows in the Special Region of Yogyakarta-Central Java from March to June 2016. The examined animals were Ongole and Local Cattle (PO) cross breed, Simmental breed, Limousin breed, Simmental and PO cross breed, PO and Limousin cross breed, Friesian Holstein breed (FH), Brahman breed, Angus breed, Angus and Brahman cross breed and Bali breed. McMaster technique, saturated NaCl flotation technique and Parfitt and Banks technique were used simultaneously in this study in order to identify the parasitic stages present in the coprological samples. The test results showed that approximately 65.93% of the cattle population was infected by parasitic stages, such as: Strongylidae (54.00%), Fasciola sp. (17.00%), Eimeria spp. (15.33%), Strongyloides sp. (4.67%), Paramphistomum sp. (4.00%), Trichuris sp. (3.67%) and Moniezia sp. (1.33%). Six different Eimeria species were identified: E. bovis, E. auburnensis, E. bukidnonensis, E. canadaensis, E. zurnii and E. cylindrica. Most of the animals presented monoinfections (79.33%), but concomitant infections were also observed (2 different parasites: 17.67%; 3 different parasites: 2.33%; more than 3 different parasites: 0.67%). With this work we proved the high level of parasitism in cattle of Central Java and we intensively highlight the need to find adequate control measures against parasitic diseases in order to reduce the detrimental impact of parasitosis in cattle.